Mitochondrial DNA analysis of a Viking age mass grave in Sweden. (September 2019) - Buś, Magdalena M.; Lembring, Maria; Kjellström, Anna; Strobl, Christina; Zimmermann, Bettina; Parson, Walther; Allen, Marie
Highlights: Mitochondrial DNA analyses were performed on Viking Age bone material. The majority of individuals in a mass grave were maternally unrelated. Individuals were assigned to West Eurasian mtDNA haplogroups. Precision ID mtDNA Whole Genome Panel was efficient for processing challenging DNA samples. Abstract: In 1998, a Viking Age mass grave was discovered and excavated at St. Laurence´s churchyard in Sigtuna, Sweden. The excavated bones underwent osteoarchaeological analysis and were assigned to at least 19 individuals. Eleven skeletons showed sharp force trauma from bladed weapons. Mass graves are an unusual finding from this time period, making the burial context extraordinary. To investigate a possible maternal kinship among the individuals, bones and teeth from the skeletal remains were selected for mitochondrial DNA (mtDNA) analysis. Sanger sequencing of short stretches of the hypervariable segments I and II (HVS-I and HVS-II) was performed. A subset of the samples was also analysed by massively parallel sequencing analysis (MPS) of the entire mtDNA genome using the Precision ID mtDNA Whole Genome Panel. A total of 15 unique and three shared mtDNA profiles were obtained. Based on a combination of genetic and archaeological data, we conclude that a minimum of 20 individuals was buried in the mass grave. The majority of the individuals were not maternally related. However, two possible pairs of siblings or mother-child relationships were identified. All individuals were assigned to West Eurasian haplogroups, with a predominance of haplogroup H. Although the remains showed an advanced level of DNA degradation, the combined use of Sanger sequencing and MPS with the Precision ID mtDNA Whole Genome Panel revealed at least partial mtDNA data for all samples.